Presence and Rights: A Response to Linda Bosniak - Kay Hailbronner (Amsterdam Law Forum, 2008)
Linda Bosniakâ€™s article â€˜Ethical Territoriality and the Rights of Immigrantsâ€™ puts forward the idea of â€œethical territorialityâ€. She uses the notion to denote the conviction that a personâ€™s physical presence within the territory of a state should be the basis for extending them important rights and recognition. The current article offers a critique to the arguments advancing such notion. Suggestions are made for an alternative legal approach towards matters on the inclusion and exclusion of immigration with the conclusion that full inclusion into the spheres of another state cannot be deducted from mere territorial presence alone.Â Â Â Â Â